Pengembangan Model “YUDI” dalam Pembelajaran Karakter SD - Purnamasari, Veryliana; Hernanda, Ardiyanto (Universitas Muhammadiyah Magelang, 2017)
The problem behind the absence of a traditional game-based gymnastics development model that can support the development of character in elementary school. Another thing that lies behind this research, the various acts of moral decline and character, especially in elementary school students who have reached low grade elementary students. The goal to be achieved through this research is to produce